FAKTOR DETERMINAN ERC DENGAN PERSISTENSI LABA SEBAGAI VARIABEL INTERVENING - Nur'aini Rokhmania; Nurul Hasanah Uswati Dewi; Pepie Diptyana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of Size, book-tax differences, debt levels and operating cash flow on Earning Response Coefficient (ERC) with Earnings Persistence as an intervening variable. ERC is measured by a coefficient that shows the estimated strength of the influence of unexpected earnings and the accumulation of abnormal returns that appear during earnings announcements. Meanwhile, Earnings Persistence is measured by the slope regression coefficient of the relationship between current earnings and the next period's earnings. The sample used is a manufacturing company listed on the Indonesia Stock Exchange (IDX) with the 2016 - 2018 observation year. The sample data collected is 243 data. Hypotheses were tested with Warp PLS. Hypothesis testing results that there are two variables that significantly affect ERC, namely Profit Persistence and Operating Cash Flow. Earnings persistence proved to have a significant negative effect while Operating Cash Flow had a significant positive effect on ERC. For variables Size, Book-Tax Difference, and Debt Level, it does not show any effect on ERC nor on Earning Persistence and Earnings Persistence is proven not to be an intervening variable.